In vitro Antitumor Activity and Electrochemical Studies of Bio-Electroactive Anthraquinone Derivatives in Glioblastoma - SUELLEN MARIA A. DA SILVA; JOÃO KAYCKE S. DA SILVA; JOICE FRAGOSO O. DE ARAÚJO; ANDRESSA LETÍCIA L. DA SILVA; ANDRESA KATHERINE A. DE ALMEIDA; TAMIRES A. DO NASCIMENTO; ANDRÉ FELIPPE A. XAVIER; RENATA G. DE ALMEIDA; GUILHERME AUGUSTI M. JARDIM; EUFRÂNIO N. DA SILVA JÚNIOR; VIVALDO MOURA-NETO; ALYSSON WAGNER F. DUARTE; et al. (Anais da Academia Brasileira de Ciências)
Abstract This study investigated the antiglioblastoma potential of nine synthetic anthraquinone derivatives (SAQDs). SAQDs were tested for their in vitro cytotoxicity against PBMCs and GBM02 cells. For PBMC, SAQDs showed no cytotoxic effects up to 100 µM. Four most promising SAQDs (1, 4, 5, and 9) demonstrated significant activity against GBM02, with selectivity index >4.54 for 1, >1.30 for 4 and 5, and >1.19 for 9. These compounds induced morphological changes, incluing cell rounding, cytoplasmic vacuolation, and membrane rupture, and inhibited cell migration. Due to the pharmacological role of oxidative stress, electrochemical methods were used to compare the reductive and oxidative capacities of the SAQD with their antitumor activity. Considering the reported findings, it is feasible to confirm that some SAQDs have antitumor effects, supporting additional studies of AQ for developing novel anticancer medications. Due to the small number of compounds investigated, it was not possible to observe a relationship between electrochemical and biological data. However, the electrochemical data are new and could be used to prepare other compounds on this line. CV data revealed that the sulfone’s electron-withdrawing effect facilitated the reduction. At the same time, the sulfides had shown less positive potential for oxidation waves due to the presence of electron-donating groups.